2016
DOI: 10.1097/sap.0000000000000856
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Burn Contracture Outcome in Developing Countries

Abstract: Burn type, age when burned, and timing of surgery were significant factors affecting hand outcomes, whereas age affected elbow outcomes, and time elapsed until surgery affected knee results. An algorithm was formulated to enable physicians in developing countries with limited resources to triage patients and optimize patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…). Following assessment, 68 articles, involving 708 032 patients across 71 LMICs, were included in the review ( Tables S1 and S2 , supporting information). Country‐specific patient numbers were reported in 60 studies but were absent from six and two provided total LMIC patient numbers only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…). Following assessment, 68 articles, involving 708 032 patients across 71 LMICs, were included in the review ( Tables S1 and S2 , supporting information). Country‐specific patient numbers were reported in 60 studies but were absent from six and two provided total LMIC patient numbers only.…”
Section: Resultsmentioning
confidence: 99%
“…a Number of studies and b number of patients in studies of LMICs. Countries with fewer than 100 patients recruited for a multinational study were excluded from a , as were studies in which LMIC‐specific patient numbers were not specified…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies on the psychological function of patients after burns at home and away, but systematic research on the QOL in patients with facial burn scars is rarely reported. Some current studies have shown that the factors affecting the quality of life of patients with facial burn scars are as follows (Finnerty et al, 2016; Polychronopoulou et al, 2018): social factors [gender, marital status, occupation, and economic status (Levi et al, 2018; Spronk et al, 2018a)] disease-related factors [effects of scarring on facial function, the degree of influence, the degree of burn, and the duration of disease (Watson et al, 2018)] and psychosocial factors (stress, suppression, social support, and disability acceptance) (Garcia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The level of patient disability acceptance increases with the duration of disability, and the patient is better able to adapt to life after the illness, so the quality of life also has a significant upward trend. The quality of life also increases significantly (Garcia et al, 2016). The reasons may be as follows.…”
Section: Introductionmentioning
confidence: 99%